Greening the Desert: Sustainability Challenges and Environmental Initiatives in the GCC States - Meredian Alam (15445439) (2023)
Oil, gas, and other minerals contribute significantly to the growth of Gulf Cooperation Council (GCC) states, however their development always affects the environment. The GCC countries are therefore taking measures to ensure economic growth, job availability, social equality, and natural resource management by incorporating environmental considerations into economic policy and aspiring for green growth at the national and regional levels. With this in mind, this chapter explores various sustainability initiatives for environmental conservation in the GCC. This chapter focuses primarily on the national efforts of each of the GCC states to prevent and control hazards and to reduce the effects of environmental challenges (such as air pollution, climate change, oil spills, and declining quality of coastal and marine environments). Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_29